Outcome of 177Lu-DOTATATE Peptide Receptor Radionuclide Therapy in Progressive Metastatic Neuroendocrine Tumors from a Tertiary Care Center - David Mathew; Saumya S. Sunny; Justin Benjamin; Junita R. John; Felix K. Jebasingh; Josh T. Georgy; Ashish Singh; Regi Oommen (Indian Journal of Endocrinology and Metabolism)
Introduction: Functioning neuroendocrine tumors (NETs) that do not respond to standard therapies are commonly considered for Peptide Receptor Radionuclide Therapy (PRRT). The benefit of 177Lu-DOTATATE PRRT in patients with progressive metastatic NET was analyzed and survival in multi-organ involvement. Methods: Forty-one patients with refractory, progressive, or advanced symptomatic NETs, with or without previous treatment modalities were studied. They were treated with 177Lu-DOTATATE IV infusion 150 mCi per dose up to four cycles. Retrospectively, they were assessed for response to PRRT based on clinical, Imaging-Contrast CT/68Ga-DOTATATE PET-CT, and biochemical markers. After treatment, classification based on disease status, symptomatic improvement, and response to treatment based on Chromogranin A level was done. The organs involved and their respective survival benefits, as estimated by Kaplan Meier, were plotted for 60 months. Results: The mean serum Chromogranin A level at baseline was 2841 U/ml (Median = 3150). The main site of primary NET was in the pancreas, and the most common site for metastases was the liver. Following PRRT, all patients, except one, reported an improvement in their baseline complaints. Most (82%) reported no new symptoms, and 50% had a reduction in serum Chromogranin A levels. Follow-up imaging showed regression in one patient, static tumor in 18, and progression in rest. Considering radiological and clinical responses, the overall benefit was noticed in 29 (70%) patients. Despite symptomatic improvement, there was no significant survival benefit for those with pancreatic, liver, or nodal metastasis. Conclusion: A majority of patients who were treated with PRRT demonstrated clinical, radiological as well as biochemical positive responses warranting an earlier consideration for this well-tolerated treatment modality.